Hoya endauensis (Asclepiadaceae) and Licuala dranifielddii (Palmae), two new species from Ulu Endau, Peninsular Malaysia - Kiew, Ruth (Malaysian Nature Society, 1989)
Two new species, Hoya endauensis Kiew (Asclepiadaceae) and Licuala dransfieldii Kiew (Palmae), are described from Ulu Endau, Johore, Peninsular Malaysia. Both are endemic to the Ulu Endau area. H. endauensis is a rare epiphyte which grows on trees by rivers and L. dransfieldii is common in the undergrowth of lowland forest.